THE ROLE OF PATIENT EXPERIENCE AND SOCIAL MEDIA MARKETING ON REVISIT INTENTION WITH BRAND AWARENESS AS A MEDIATION VARIABLE IN GENERAL OUTPATIENT PATIENTS AT PRIVATE CLASS B HOSPITALS IN TANGERANG CITY - Ditha Sari Pratiwi, Rina Anindita, Idrus Jus’at (Integrative Perspectives of Social and Science Journal, 2025)
Good healthcare quality is reflected in the intention to revisit a hospital. Revisiting intention leads to an increase in the number of patients visiting and the performance of a hospital organization. This study aims to investigate the impact of patient experience and social media marketing on revisit intention, with brand awareness serving as a mediator. The research method is quantitative, causal, and conducted over a specific period. Respondents were 100 general outpatients from Private Class B Hospitals in Tangerang. Data analysis methods used the three-box method and PLS SEM. The results found a simultaneous influence of patient experience, social media marketing, and brand awareness on revisit intention. Patient experience, social media marketing, and brand awareness each have a positive influence on revisit intention. Patient experience and social media marketing have a positive impact on brand awareness. There is a mediating effect of brand awareness on the relationship between patient experience and revisit intention. Brand awareness also mediates the influence of social media marketing on revisit intention. Management should prohibit doctors from sharing things that make patients feel anxious and afraid. Management should recruit someone with expertise in digital marketing to enhance the quality of content on Private Class B Hospitals' Instagram account in Tangerang. It's essential to enhance brand awareness by delivering exceptional service through friendly staff and prompt wait times. Management must provide a positive patient experience while providing healthcare, improve the quality of their Instagram content, and increase brand awareness.